Synthesis of 1,3-Dehydroadamantanes Possessing Alkyl, Phenyl, and Alkoxy Substituents by Intramolecular Wurtz-Type Coupling Reaction of 1,3-Dibromoadamantanes - Inomata, Sotaro; Harada, Yusuke; Nakamura, Yuya; Nakamura, Taisuke; Ishizone, Takashi (Synthesis, 2013)
A series of highly strained [3.3.1]propellane derivatives, 1,3-dehydroadamantanes (DHAs) possessing alkyl, phenyl, and alkoxy substituents, such as 5-butyl, 5-hexyl, 5-octyl, 5-phenyl, 5-methoxy, 5-butoxy, 5,7-dimethyl, 5-ethyl-7-hexyl, 5,7-dibutyl-, 5-butyl-7-isobutyl, 5-butyl-7-hexyl, 5-butyl-7-phenyl, 5-butyl-7-methoxy, and 5-butoxy-7-butyl, were synthesized in several gram amounts. The 1,3-dibromoadamantanes carrying alkyl, phenyl, and alkoxy substituents were converted into the corresponding DHAs via the intramolecular Wurtz-type coupling reactions with lithium metal in THF in 21–81% yields.
Keywords: 1,3-dehydroadamantanes; 1,3-dibromoadamantanes; Wurtz coupling reaction; [3.3.1]propellanes